From Information to Message: Archaeology and Media in Serbia - Jasna Vuković (University of Belgrade, 2016)
The paper discusses the image of archaeology and archaeologists created in the public by various media. On the grounds of analysis of the texts in which the subject of archaeology figures in newspapers and on social networks, it is demonstrated that archaeologists are mainly perceived in the public as inert “concealers” of the real truth of the past. The reason behind this is equally in the insufficient knowledge of the media, but as well in the reluctance of professional archaeologists to communicate. The paper offers an outline of long-term strategy to bridge the existing gap and inform the public about the mission and social relevance of the discipline.